PENGARUH KINERJA KEUANGAN DAN MANAJEMEN LABA TERHADAP NILAI PERUSAHAAN PADA PT SOLUSI BANGUN INDONESIA TBK PERIODE 2014-2024 - Rifaldy Bagas Prasetio; Wirawan Suryanto (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
Abstract. This study aims to analyze the influence of Financial Performance and Earnings Management on Firm Value at PT Solusi Bangun Indonesia Tbk for the period 2014 – 2024, both partially and simultaneously. The method used is quantitative, with data obtained from the Indonesia Stock Exchange official website (www.idx.co.id) and the official website of PT Solusi Bangun Indonesia Tbk. The results of this study indicate that the Financial Performance variable has a t-statistic of 2.926 > t-table 2.30600 with a significance value of 0.019 < 0.05; th v us, it can be concluded that Financial Performance (X1) has a significant effect on Firm Value (Y). The Earnings Management variable has a t-statistic of 0.604 < t-table 2.30600 with a significance value of 0.562 > 0.05, suggesting that Earnings Management (X2) does not have a significant effect on Firm Value (Y). Furthermore, the F-test results show an F-statistic of 4.311 < F-table 4.459 with a significance value of 0.054 > 0.05, meaning that Financial Performance and Earnings Management simultaneously do not have a significant effect on Firm Value Keywords: financial performance, earnings management, firm value